2018
DOI: 10.1142/s0218271818300021
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolynomial Lagrangian approach to regular black holes

Abstract: We present a review on Lagrangian models admitting spherically symmetric regular black holes (RBHs), and cosmological bounce solutions. Nonlinear electrodynamics, nonpolynomial gravity, and fluid approaches are explained in details. They consist respectively in a gauge invariant generalization of the Maxwell–Lagrangian, in modifications of the Einstein–Hilbert action via nonpolynomial curvature invariants, and finally in the reconstruction of density profiles able to cure the central singularity of black holes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 161 publications
0
18
0
Order By: Relevance
“…In the two-dimensional case, the most general dilatonic action to give the second-order field equations is known and one can construct the action from a given metric of a non-singular black hole [22,83]. In fact, this most general two-dimensional dilatonic action can be obtained by a dimensional reduction imposing spherical symmetry from an n(≥ 4)-dimensional action made of non-polynomial curvature invariants [84,85]. On the other hand, it was shown that the Hayward black hole can be a solution in Degenerate Higher-Order Scalar-Tensor (DHOST) theories [86], which is a generalization of the most general scalar-tensor theory with the second-order field equation, the Horndeski theory, not to suffer from the Ostrogradsky ghost instability.…”
Section: Propositionmentioning
confidence: 99%
“…In the two-dimensional case, the most general dilatonic action to give the second-order field equations is known and one can construct the action from a given metric of a non-singular black hole [22,83]. In fact, this most general two-dimensional dilatonic action can be obtained by a dimensional reduction imposing spherical symmetry from an n(≥ 4)-dimensional action made of non-polynomial curvature invariants [84,85]. On the other hand, it was shown that the Hayward black hole can be a solution in Degenerate Higher-Order Scalar-Tensor (DHOST) theories [86], which is a generalization of the most general scalar-tensor theory with the second-order field equation, the Horndeski theory, not to suffer from the Ostrogradsky ghost instability.…”
Section: Propositionmentioning
confidence: 99%
“…Based on that work, a number of universal results were obtained for the free energy of odd-dimensional CFTs on squashed spheres [40]. See, for example, [41][42][43][44][45][46] for a number of other recent developments and applications of these -and closely related -theories.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest possible case of that kind, and the first to be identified, corresponds to a single additional cubic term and goes by the name of four-dimensional Einsteinian cubic gravity 1 (ECG) [10], whose action is given in (8) below. Many examples of GQTG theories in general dimensions have now been constructed, and their respective black hole solutions studied and characterized [11][12][13][14][15][16][17][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%